“DEVELOPING CREATIVE THINKING AND VISUAL LITERACY IN CHILDREN THROUGH NATIONAL GAMES IN FINE ARTS LESSONS” - Xidoyeva Mahliyo Bozor qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article analyzes the role of national games in developing creative thinking and visual literacy in children during fine arts lessons. National games stimulate children’s imagination, rhythm perception, spatial awareness, and emotional expression, helping them make independent artistic decisions. The article also highlights pedagogical and methodological approaches for organizing lessons based on traditional games.